Implementação de um Plano de Manutenção Preventiva numa Unidade de Produção de Cerveja - Pedro Miguel Fazenda Bastos (2017)
This report is part of the Dissertation in Business Environment of the 5th year of the Integrated Master in Electrical and Computer Engineering (MIEEC), Automation and specialization in Industrial Management, Faculty of Engineering, University of Porto. The project was conducted at the Maintenance Department of UNICER Bebidas, SA, in the center of Leça do Balio, and covers the implementation of preventive maintenance in SAP-PM, focusing on the standardization of procedures, planning of tasks and on the teaching of the SAP tool, Plant Maintenance module, to all stakeholders in the company's maintenance process. An equipment is subject to have their normal operating conditions degraded over time, either by its use or even by fortuitous causes, being the maintenance process the part responsible for restoring them to correct and acceptable levels. In this way, the maintenance tries to resort to a diverse set of tasks, selected and programmed according to the characteristics and use of the object. The main goals of the project involve the implementation of preventive maintenance in critical equipment of the company, the uniformity of knowledge and the standardization of processes, in order to have a more rigorous use of the SAP tool in support to the Maintenance service of the company. In this way, the existing transactions were improved, preventive plans were created for critical equipment identified by UNICER Bebidas, SA and a SAP-PM manual was created, which will serve as support to the maintenance technicians and main "customers" involved in the process, which are the "Production" and "Filling" areas.